Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1002/(sici)1097-4636(19970615)35:4<505::aid-jbm10>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of hydrolysis of polydimethylsiloxane (PDMS)

Abstract: Silicones (polydimethylsiloxane, PDMS) are the materials currently used in most breast implants. ICP and FTIR analysis of the tissue capsule around aged breast implants and in vitro models show that Si-containing material is leaking from the PDMS implants. In this study, the hydrolysis of PDMS has been theoretically modeled using a semiempirical quantum mechanical method called AM1. The activation barrier for removing a methanol monomer was found to be +82 Kcal/mol while the removal of a methane monomer was +4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the future, it will be interesting to use SFG spectroscopy on isotope-labeled PDMS samples to elucidate detailed mechanistic pathways since it is possible that multiple multistep chemical reactions may be occurring at the same time. At the present time, we can only speculate on possible mechanisms for regeneration of CH 3 groups on the basis of our results and published literature. , It has been suggested that the attack of radicals containing CH 3 groups, the reorientation of PDMS molecules at the surface during modification, and migration of PDMS molecules (or oligomers) from the bulk during modification could all contribute to CH 3 group regeneration. In our SFG experiments, we observe no significant change in reorientation of PDMS molecules at the surface during modification.…”
Section: Resultsmentioning
confidence: 69%
“…In the future, it will be interesting to use SFG spectroscopy on isotope-labeled PDMS samples to elucidate detailed mechanistic pathways since it is possible that multiple multistep chemical reactions may be occurring at the same time. At the present time, we can only speculate on possible mechanisms for regeneration of CH 3 groups on the basis of our results and published literature. , It has been suggested that the attack of radicals containing CH 3 groups, the reorientation of PDMS molecules at the surface during modification, and migration of PDMS molecules (or oligomers) from the bulk during modification could all contribute to CH 3 group regeneration. In our SFG experiments, we observe no significant change in reorientation of PDMS molecules at the surface during modification.…”
Section: Resultsmentioning
confidence: 69%
“…These can be produced from a proposed reaction mechanism involving water interacting with Si–H groups; although the hydrosilylation reaction is an addition reaction between Si–H and vinyl groups in the presence of a catalyst, notably Pt, water can also attack Si–H to form Si-OH in the presence of the same catalyst [ 17 , 34 ]. Additionally, siloxanols can be created from the hydrolysis of PDMS, where a water molecule attacks a siloxane chain, resulting in a chain scission and two hydroxyl-terminated chains [ 74 , 75 , 76 ]. If a siloxanol encounters a silane, a new crosslink will form between the two moieties and H 2 gas will be produced.…”
Section: Resultsmentioning
confidence: 99%
“…The AM1 calculation could yield to molecular structures, heats of formation, and transition-state energies. According to the procedure recommended by West et al, the conformations of an intermediate for the hydrolysis and condensation were built by binding the oxygen atom of a nucleophilic complex to the silicon atom of an alkoxysilane and hydroxysilane, respectively, and then minimizing the energy with AM1 unrestricted Hartree−Fock (UHF). These UHF AM1-optimized geometries then were submitted to MOPAC saddle-point calculations to predict the transition state.…”
Section: Methodsmentioning
confidence: 99%